EXPLORING INDONESIAN TEACHER PROFESSIONAL EDUCATION PROGRAM (PPG) DEVELOPMENT IN MANAGING CLASSROOM - Cindi Martina Marbun; Nariza Ayu Pasha; Fidya Felinda Ilahude; Azwar Abbas (IKIP Siliwangi, 2024)
Teachers are required to have the ability to manage the classroom so that the learning and teaching process can run conducively. However, research investigating classroom management is scarcely reported. This study aims to explore the challenges faced by Teacher Professional Education (PPG) program students and their perception after participating in the PPG program to their ailment in managing classrooms. The participants in this qualitative research were three PPG students from various universities in Indonesia. Open questionnaires and interviews were used to collect data. The findings show that there are three main challenges faced by PPG students, namely speaking to students and handling their responses, creating the setting, and communicating the rules to the students. Then, after they participate in the PPG program, they perceive that they are more communicative, innovative, creative, and more aware of students' needs.